Congenitally missing maxillary permanent canines: report of 32 cases from an ethnic Chinese population - S. Y. CHO, C. K. LEE & J. C. Y. CHAN (Paediatric Dentistry, 2004)
Cases of congenitally missing permanent teeth involving only maxillary canines are uncommon.